Energy transduction in the methanogen Methanococcus voltae is based on a sodium current. - Dybas, M (1992)
We provide experimental support for the proposal that ATP production in Methanococcus voltae, a methanogenic member of the archaea, is based on an energetic system in which sodium ions, not protons, are the coupling ions. We show that when grown at a pH of 6.0, 7.1, or 8.2, M. voltae cells maintain a membrane potential of approximately -150 mV. The cells maintain a transmembrane pH gradient (pH(in) - pH(out)) of -0.1, -0.2, and -0.2, respectively, values not favorable to the inward movement of protons. The cells maintain a transmembrane sodium concentration gradient (sodium(out)/sodium(in)) of 1.2, 3.4, and 11.6, respectively. While the protonophore 3,3',4',5-tetrachlorosalicylanilide inhibits ATP formation in cells grown at pH 6.5, neither ATP formation nor growth is inhibited in cells grown in medium at pH 8.2. We show that when grown at pH 8.2, cells synthesize ATP in the absence of a favorably oriented proton motive force. Whether grown at pH 6.5 or pH 8.2, M. voltae extrudes Na+ via a primary pump whose activity does not depend on a proton motive force. The addition of protons to the cells leads to a harmaline-sensitive efflux of Na+ and vice versa, indicating the presence of Na+/H+ antiporter activity and, thus, a second mechanism for the translocation of Na+ across the cell membrane. M. voltae contains a membrane component that is immunologically related to the H(+)-translocating ATP synthase of the archaeabacterium Sulfolobus acidocaldarius. Since we demonstrated that ATP production can be driven by an artificially imposed membrane potential only in the presence of sodium ions, we propose that ATP production in M. voltae is mediated by an Na+-translocating ATP synthase whose function is coupled to a sodium motive force that is generated through a primary Na+ pump.